ANALISIS KEPERCAYAAN DAN KEPUTUSAN PEMBELIAN DI CAFE UMI AYUE - Daniel Napitupulu; Osman Manalu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to investigate the influence of trust on purchasing decisions at Café Umi Ayue. Consumer trust in a brand or place can play an important role in the purchasing process. In the context of cafes, consumer confidence in the quality of products, service, cleanliness and reputation of cafes can influence their decisions to purchase and return to visit. This research uses a quantitative descriptive approach by distributing questionnaires to visitors to Café Umi Ayue. The research sample consisted of cafe visitors who were randomly selected. Data analysis was carried out using the regression method to determine the extent to which consumer trust influences their purchasing decisions at Café Umi Ayue. It is hoped that the results of this research will provide better insight into the factors that influence consumer purchasing decisions in cafes, especially in the context of trust. The practical implications of this research can help Café Umi Ayue management in increasing consumer confidence through more effective marketing strategies and quality service.